2022
DOI: 10.4018/jitr.299919
|View full text |Cite
|
Sign up to set email alerts
|

A Dynamic Strategy for Classifying Sentiment From Bengali Text by Utilizing Word2vector Model

Abstract: In today's world, around 230 million people used the Bengali or Bangla language to communicate. These individuals are progressively associated with online exercises on famous micro-blogging and long-range interpersonal communication locales, imparting insights what's more, musings, and also the vast majority of articles are in the Bengali language. Thus, Bengali people express their emotions using the Bangla language by reviewing, commenting, or recommendations. Sentiment analysis helps determine the people's … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Compared to the few studies conducted on multiclass sentiment analysis in Bangla using deep learning, the efficacy of our proposed approach with Bangla-BERT is significantly improved. In our dataset, Bangla-BERT classified multiclass sentiments with 88.78% accuracy, which is higher than previously proposed deep learning methods [15,35,36].…”
Section: A Insights and Implicationsmentioning
confidence: 56%
“…Compared to the few studies conducted on multiclass sentiment analysis in Bangla using deep learning, the efficacy of our proposed approach with Bangla-BERT is significantly improved. In our dataset, Bangla-BERT classified multiclass sentiments with 88.78% accuracy, which is higher than previously proposed deep learning methods [15,35,36].…”
Section: A Insights and Implicationsmentioning
confidence: 56%
“…Here, real IMDB and Amazon data sets were employed to estimate the suggested method performance. Similarly many approaches related to multi class sentiment classification [23][24][25][26][27] has been done in the previous studies but all those methods require better performance in terms of accuracy and the summary of literature review is presented in table 1 as shown below.…”
Section: Cognitive-inspired Domain Adaptationmentioning
confidence: 99%
“…They employed BERT, a language model, to tackle this issue and achieved a commendable accuracy of 88%, demonstrating its effectiveness. Finally, a study conducted by the authors [29] investigated the application of Skip-gram for multiclass comment classification. The results of this study indicated that an accuracy rate of 75% was achieved.…”
Section: Literature Reviewmentioning
confidence: 99%